Dibalik Nilai Perusahaan: Firm Size, Profitability, Leverage, Growth Opportunity dan Current Ratio - Fadellatur Ramadhani Haryasih; Mujiyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Firm value represents the strength of a company in the eyes of investors, showcasing its ability to compete with other companies. A higher firm value reflects better quality and is more likely to serve as a positive signal to investors. This study aims to analyze the effect of firm size, profitability, leverage, growth opportunities, and current ratio on firm value in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) for the 2018–2022 period. The research employs a quantitative approach using secondary data derived from the companies’ annual financial statements. The sample comprises 54 companies selected through purposive sampling based on specific criteria. Data analysis was conducted using multiple linear regression. The results indicate that firm size and growth opportunities do not have a significant effect on firm value. Conversely, profitability, leverage, and current ratio significantly influence firm value. This study is limited by the scope of its sector, observation period, and the number of variables examined. Future research is recommended to broaden the scope of objects, extend the observation period, and incorporate additional variables to achieve more comprehensive findings.